Functionalization of graphene nanostructures with inorganic nanoparticles and their use for the removal of pharmaceutical pollutants in water - Oliveras, Jana; Marcon, Lionel; Bastús, Neus G.; Puntes, Victor (Frontiers in Chemical Engineering, 2022)
Emerging pollutants such as pharmaceuticals are of special concern because despite their low environmental concentration, their biological activity can be intense, and they should be prevented to reach uncontrolledly to the environment. A graphene-based hybrid material decorated with Fe3O4 and TiO2 nanoparticles (NPs) has been prepared to effectively remove emerging pollutants as nonsteroidal anti-inflammatory drugs (NSAIDs) Ibuprofen and Diclofenac present in water at low environmental concentrations by a one-step functionalization process following a novel gentle and scalable surfactant depletion approach. Following this methodology, nanoparticles are progressively deprived of their original surfactant in the presence of graphene, leading to the formation of hybrid nanostructures composed of two different types of nanoparticles well dispersed over the graphene nanosheets. Ibuprofen and Diclofenac adsorption kinetics on the composites was investigated via UV-Vis spectroscopy. The as prepared hybrid material possesses high adsorption capacity, superparamagnetic properties, photocatalytic behavior, and good water dispersibility. Thanks to incorporating TiO2 nanoparticles as in situ catalysts, the adsorption performance of composites is restored after use, which could be a promising recycling pathway for the adsorbents in wastewater treatments.